Correction: Dengue illness impacts daily human mobility patterns in Iquitos, Peru. - Kathryn L Schaber; Valerie A Paz-Soldan; Amy C Morrison; William H D Elson; Alan L Rothman; Christopher N Mores; Helvio Astete-Vega; Thomas W Scott; Lance A Waller; Uriel Kitron; John P Elder; Christopher M Barker; et al. (Public Library of Science (PLoS), 2020)
[This corrects the article DOI: 10.1371/journal.pntd.0007756.].